Molecular basis of accessible plasma membrane cholesterol recognition by the GRAM domain of GRAMD1b - Ercan, Bilge (2022)
Cholesterol is essential for cell physiology. Transport of the "accessible" pool of cholesterol from the plasma membrane (PM) to the endoplasmic reticulum (ER) by ER-localized GRAMD1 proteins (GRAMD1a/1b/1c) contributes to cholesterol homeostasis. However, how cells detect accessible cholesterol within the PM remains unclear. We show that the GRAM domain of GRAMD1b, a coincidence detector for anionic lipids, including phosphatidylserine (PS), and cholesterol, possesses distinct but synergistic sites for sensing accessible cholesterol and anionic lipids. We find that a mutation within the GRAM domain of GRAMD1b that is associated with intellectual disability in humans specifically impairs cholesterol sensing. In addition, we identified another point mutation within this domain that enhances cholesterol sensitivity without altering its PS sensitivity. Cell-free reconstitution and cell-based assays revealed that the ability of the GRAM domain to sense accessible cholesterol regulates membrane tethering and determines the rate of cholesterol transport by GRAMD1b. Thus, cells detect the codistribution of accessible cholesterol and anionic lipids in the PM and fine-tune the non-vesicular transport of PM cholesterol to the ER via GRAMD1s.